Sensitive quantification of m.3243A>G mutational proportion in non-retinal tissues and its relationship with visual symptoms. Issue 5 (30th September 2021) - Mullin, Nathaniel K; Anfinson, Kristin R; Riker, Megan J; Wieland, Kelsey L; Tatro, Nicole J; Scheetz, Todd E; Mullins, Robert F; Stone, Edwin M; Tucker, Budd A
Abstract: The m.3243A>G mutation in the mitochondrial genome commonly causes retinal degeneration in patients with maternally inherited diabetes and deafness and mitochondrial encephalopathy, lactic acidosis and stroke-like episodes. Like other mitochondrial mutations, m.3243A>G is inherited from the mother with a variable proportion of wild type and mutant mitochondrial genomes in different cells. The mechanism by which the m.3243A>G variant in each tissue relates to the manifestation of disease phenotype is not fully understood. Using a digital PCR assay, we found that the % m.3243G in skin derived dermal fibroblasts was positively correlated with that of blood from the same individual. The % m.3243G detected in fibroblast cultures remained constant over multiple passages and was negatively correlated with mtDNA copy number. Although the % m.3243G present in blood was not correlated with severity of vision loss, as quantified by Goldmann visual field, a significant negative correlation between % m.3243G and the age of onset of visual symptoms was detected. Altogether, these results indicate that precise measurement of % m.3243G in clinically accessible tissues such as skin and blood may yield information relevant to the management of retinal m.3243A>G-associated disease.